Analysis of the Challenges of Implementing a Carbon Tax in Efforts to Reduce Greenhouse Gas Emissions and Achieve Net Zero Emissions in Indonesia - Fajriyah Melati Sholihah; Etty Puji Lestari; Heffi Christya Rahayu (Jurnal Ilmu Sosial Mamangan, 2024)
The main source of market failure from fossil fuels is the emergence of negative externalities such as air pollution and climate change. Without a carbon tax, consumers do not pay the entire cost of consumption of a product, including costs associated with production, shipping, and social costs such as lost income due to air pollution and climate change. Indonesia's efforts to reduce emissions from greenhouse gases and achieve net zero emissions are part of Indonesia's commitment to the global agreement between countries on actions to combat climate change, which can be achieved through the introduction of a tax on carbon in the country. Nevertheless, carbon taxes have their pros and cons in society. This study aims to examine the challenges of implementing a carbon tax in an effort to reduce emissions from greenhouse gases and obtain zero or net emission results in Indonesia. This research uses a qualitative research approach for its research. This study used a qualitative methodology based on the use of descriptive analytical techniques, which specifically summarized the conclusions drawn from the data collected and subsequently examined. The secondary data source of this research is used together with literature review research instruments, namely data collection through literature review and documentation. Data analysis in this study used an interactive model consisting of three activity streams simultaneously: data presentation, data condensation, and conclusion/verification. The results of the analysis explain that the implementation of a carbon tax that has the aim of changing the behavior of economic actors to move to relatively low-carbon green economic activities is a mitigation measure that is quite effective in minimizing greenhouse gas emissions and achieving " net zero emissions" in Indonesia with challenges that must be faced such as the involvement of business people in the prevailing democratic political system, good conditions and poor management of government institutions, the response to behavior change and high trust from the public, the emergence of concerns about the effect of carbon tax implementation on business sector conditions including increases in production prices, financial burdens and competitiveness.